MAF proteins: a family of regulating and regulated molecules - Simile, Maria Maddalena; Latte, Gavinella; Pascale, Rosa Maria (Digestive Medicine Research, 2018)
The proteins of MAF family (the cellular counterpart of viral oncogene MAF, isolated from avian musculoaponeurotic fibrosarcoma) are transcription factors regulating gene expression. On the bases of the size, they are sub-grouped into two families: the “large” (L-MAFs: MAFA, MAFB, c-MAF, and Nrl) and the “small” (S-MAFs: MAFF, MAFK, and MAFG) MAF proteins (1).